INTERNSHIP MANAGEMENT INFORMATION SYSTEM AT FOUNDATION FOR FOSTERING DISABLED CHILDREN SURAKARTA IN OPTIMIZING SCHOOL DATA - Sophisticated Ajika Pamungkas; Narendra Rivando Axel S.; Dhafa Gigih Iskandar; Samuel Rahmat Sanjaya; Muhammad Akbar; Keke Dyah Arlita; Surya Imam Prasetyo; Nugraheni Wijayanti; Meylinda Putri Ayu M; Bardi Pratama; Wasis Waluyo; Wishnu Wibowo (PT. Media Akademik Publisher, 2025)
The system running at YPAC School Surakarta still uses a manual method. Students come to the partner's place to submit documents to the partner. In my opinion, this kind of anddata management is less effective and efficient in terms of travel time and costs because many students live far from the internship location. Monitoring students is also not optimal because the Director is often not at home because of her job as a teacher who is required to leave early and return late so that she cannot monitor students optimally. The data collection methods used are observation, interviews, literature studies, and documentation. The development method in the system uses the waterfall method which includes the stages of system analysis, system design, writing program code, program testing, and program implementation. This management information system is website-based using the PHP programming language and MySQL database. The Internship Management Information System and Internship Monitoring Based on the Website can help Pimpinans and Students to be more efficient in terms of time and energy, optimize costs, and improve the quality of internship programs. The internship registration and monitoring information system can improve the efficiency of energy, time, and costs incurred.